Letter from the Navy 1977 - John T. Dick-Peddie:::Captain, U.S. Navy::: (1977)
A letter from the Department of the Navy Officer in Charge of Construction rejecting a proposed review date extenstion for an Environmental Impact report discussing a proposed petroleum pipeline.